توجهات السياسة النقدية في الجزائر في إطار تعديلات قانون النقد والقرض 90- 10 - دراسة تحليلية - مصداع, راضية; بودبودة, زهرة (جامعة الوادي - University of Eloued, 2022)
شهد الاقتصاد الجزائري منذ سنة 2000 تطورات هامة جعلته يعيش في بحبوحة مالية انعكست على جوانب الاقتصاد الوطني، ورغم التطور والتحسن الذي شهده النظام المصرفي الجزائري بعد صدور قانون النقد والقرض 90-10، إلاّ أن السلطات الجزائرية لجأت إلى إجراء جملة من التعديلات عليه من أجل التأثير على مسار السياسة النقدية المنتهجة، وجعلها أكثر مسايرة للوضع النقدي السائد، وتهدف هذه الدراسة إلى تحليل وتقييم توجهات السياسة النقدية المنتهجة في الجزائر في ظل التعديلات التي شهدها قانون النقد والقرض بعد سنة 2000. وقد توصلت الدراسة إلى أن منذ بداية الإصلاحات النقدية مسايرة للتغيرات التي تشهدها أسعار النفط في السوق العالمية، فقد عرفت الكتلة النقدية في الجزائر تزايد مستمر، ولكن السياسة النقدية المنتهجة عبر أدواتها المختلفة استطاعت امتصاص الكتلة النقدية الزائد عن حاجة الاقتصاد الوطني، مما ساهم في المحافظة على الاستقرار النقدي والحد من عودة الآثار السلبية للضغوط التضخمية في الاقتصاد. Abstract: Since 2000, the Algerian’s economy has witnessed significant developments that made it lives in financial freedom that was reflected in the aspects of the national economy. Despite the development and improvement of the Algerian banking system after the issuance of the Monetary and Loan law 90-10, the Algerian authorities resorted to a number of amendments to influence the course of monetary policy adopted, making it more consistent with the prevailing monetary situation, the Monetary and Loan Act after 2000. The study concluded that since the beginning of the monetary reforms in line with the changes in oil prices in the international market, the monetary bloc in Algeria has witnessed a continuous increase, but the monetary policy adopted through its various instruments was able to absorb the monetary mass in excess of the needs of the national economy, which contributed to maintaining monetary stability and limiting the return of negative effects of inflationary pressures on the economy.
Keywords: السياسة النقدية ; قانون النقد والقرض ; الإصلاحات النقدية ; monetary policy ; Monetary and Loan Act ; Monetary reforms